Establishing the Coordination Chemistry of Antimony(V) Cations: Systematic Assessment of Ph4Sb(OTf) and Ph3Sb(OTf)2 as Lewis Acceptors. Issue 21 (15th April 2015) - Robertson, Alasdair P. M.; Chitnis, Saurabh S.; Jenkins, Hilary A.; McDonald, Robert; Ferguson, Michael J.; Burford, Neil
Abstract The coordination chemistry of the stiboranes Ph4Sb(OTf) (1 a, OTf = OSO2CF3) and Ph3Sb(OTf)2 (3) with Lewis bases has been investigated. The significant steric encumbrance of the Sb center in 1 a precludes interaction with most ligands, but the relatively low steric demands of 4‐methylpyridine‐N‐oxide (OPyrMe) and OPMe3 enabled the characterization of [Ph4Sb(OPyrMe)][OTf] (2 a) and [Ph4Sb(OPMe3)][OTf] (2 b), rare examples of structurally characterized complexes of stibonium acceptors. In contrast, 3 was found to engage a variety of Lewis bases, forming stable isolable complexes of the form [Ph3Sb(donor)2][OTf]2 [donor=OPMe3 (6 a), OPCy3 (6 b, Cy=cyclohexyl), OPPh3 (6 c), OPyrMe (6 d)], [Ph3Sb(dmap)2(OTf)][OTf] (6 e, dmap=4‐(dimethylamino)pyridine) and [Ph3Sb(donor)(OTf)][OTf] [donor=1, 10‐phenanthroline (7 a) or 2, 2′‐bipy (7 b, bipy=bipyridine)]. These compounds exhibit significant structural diversity in the solid‐state, and undergo ligand exchange reactions in line with their assignment as coordination complexes. Compound 3 did not form stable complexes with phosphine donors, with reactions instead leading to redox processes yielding SbPh3 and products of phosphine oxidation.